Blockchain Innovation: Current and Future Viewpoints for the Travel Industry - Untung Rahardja; Qurotul Aini; Sabda Maulana (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2021)
Disintermediation of the travel industry in the modern area has the most powerful and successful innovation, obviously with the assistance of Blockchain innovation. The market structure has changed since the appearance of online travel planners. Determined to improve the system for the travel industry that as of now depends on this blockchain innovation, for which the reason for this paper was made, a subjective strategy with semi-organized meetings appears to be appropriate to decide the ideal use to draw out the fundamental capability of this blockchain innovation for the business. the travel industry as per specialists. From the consequences of meetings led just as from the aftereffects of considering the impact of blockchain on business, it tends to be inferred that blockchain innovation is a fitting new advance as far as restricting and forbidding new go betweens in the entrance of the travel industry, subsequently it will prompt the vanishing of go-betweens from the travel industry market and an increment in the framework straightforward that everybody knows.